Avaliação da força muscular respiratória e desempenho físico funcional em idosos com e sem dinapenia - Leão, Gabriela Carvalho (2021)
Introduction: The reduction in muscle strength related to aging can be characterized as dynapenia which, is the first point to be observed on aging and can also cause a reduction in respiratory function and mobility limitations. Objective: the present study aimed to assess respiratory function and functional physical performance in elderly people with and without dynapenia. Methodology: It’s a cross-sectional study with 140 elderly people over 60 years of age, independent and active. A sociodemographic questionnaire was described. The tests used was: handgrip strength (HGS) for screening dynapenia, assessment of maximal inspiratory pressure (MIP) and expiratory pressure (MEP), peak expiratory flow (PEF) and the Timed up and go test (TUG). The elderly were separated into groups with and without dynapenia, as a result of the HGS assessment. Mann Whitney U and test T was used to compare variables. Results: Twenty six were considered to have dynapenia, while 114 a hundred and fourteen were considered to be without dynapenia. When the groups were compared, there was a significant difference in the variables TUG (p = 0.003), MEP (p = 0.046), MIP (p = 0.008) and PFE (p = 0.025). Conclusion: Given the above, it can be said that elderly people with dynapenia have lower values of pulmonary function and functional physical performance when compared with the elderly without dynapenia.